Behind the Scene of Soviet Runway Fashion: Capital and Position in the Field - Iuliia Papushina (Journal of Economic Sociology, 2020)
This paper presents an approach to describe and analyze the accumulation of specific capital in a Soviet design organization during the late Soviet period from 1968 to 1982. Compared to the Stalin and Thaw periods, the system of fashion production under Late Socialism is less explored. The functioning of regional clothing design houses which constituted a specific feature of the Soviet system of fashion production during this period is underexplored as well. As far as we know, this study is the first attempt to apply Bourdieu’s theory of the field of production to Soviet fashion production. Researchers do not typically use sociological theories of production to analyze Soviet fashion. The study denotes the categories of specific capital, hierarchies, and dynamics of the field of production. The system of fashion production in the late Soviet period is considered a very particular case in a non-capitalist society. There are two components of the study. The first one reconstructs the hierarchy of the Soviet system of fashion production. The second one describes professional strategies to accumulate specific capital and to occupy a position in the field of production. The study focuses on two cases of development and presentation of clothing collections by Perm Clothing Design House during union and cluster meetings of designers from 1968 to 1969 and 1979 to 1982. The paper relies on published research on Soviet fashion history, archive documents from the Russian State Economic Archive and State Archive of Perm Territory, and in-depth interviews with former employees of the Perm Clothing Design House. The results discuss the applicability of the term of “specific capital” to the explanation of the construction processes of hierarchies in the late Soviet field of fashion production. The paper contributes to the earlier conclusions on the ambiguities of Soviet fashion policy. It also introduces the definition of “specific capital” as official representatives’ appreciation of the balance between an officially approved seasonal fashion trend and the creative search achieved by designers of a certain design house. It suggests that a weird combination of socialist and pseudo-market practices penetrated and restricted Soviet fashion production.